(3GdbjGOI GdGOGQjI (B/s - (3GdYdGb, HTjQs ((3YeGf(B: s (3OGQ GdjGRhQj(B, s, 2010)
(3JYQja GdGOQGI , egGQGJgG , bhI JCKjQgG , eQGcRgG CfeGWgG h UaGJgG , GNJjGQ GdbGOI GdGOGQjjf h GdGNWGA GdQFjSjI aj YedjI GdJbjje , fXQjGJ GdbjGOI CgejJgG h eJWdHGJgG h YfGUQgG , GdaQb Hjf GdbjGOI h GdGOGQI , hGLHGJ GdbjGOI h GcJTGa GdYfGUQ GdbjGOjI , eaghe GdJhLjg , eHOC ZQV GdJhLjg h YedjI GdJhLjg , CSS GdJhLjg h QcGFRg , GdbjGOI h GJNGP GdbQGQGJ h GdMGdGJ GdeDKQI aj UfGYI h GJNGP GdbQGQ , GdGgOGa h UfGYI GdbQGQ , GdbjGOI h GOGQI GdJZjjQ h OhQ GdbjGOI aj HfGA GdaQjb h GdYdGbI Hjf GdGJUGd h GdbjGOI h GdGJUGd hab fhY GdQSGdI GdGJUGdjI hhab GJLGgGJg , GdGJUGdGJ ZjQ GdQSejI h THcGJ GJUGd GdaQjb h GdGJUGdGJ GdNGQLjI , eY hLhO CSFdI efGbTI aj fgGjI cd aUd(B.s
(3eQGLY U(B.211s
Keywords: (3GdGOGQIs; (3GdbQGQGJ GdGOGQjIs; (3GdbjGOIs